Propriedades vibracionais de cristais de Pilocarpina.HCl, Pilosina e Epiisopilosina por Espectroscopias FT-Raman, FT-IR e cálculos Ab Initio - Bento, Ricardo Rodrigues de França (2007)
This work describes the study of three alkaloids extracted from Pilocarpus Microphyllus (Rutaceae): pilocarpine (usefull in controling the desease of glaucoma), pilosine and epiisopilosine. The measurements employed FT-Raman and FT-IR spectroscopies in order to observe a complete set of normal modes of vibration of these materials. The pilocarpine investigated here was pilocarpine.HCl, that crystalazes in the monoclinic structure, space group with two HCl units and two pilocarpine molecules per unit cell. Pristine pilosine and epiisopilosine were isolated prior to their use in the crystallization process. First principles calculations were performed and the results used to assign the bands in the vibrational spectra of all three materials. Low temperature Raman measurements were performed in the case of pilocarpine clorohydrate and the results indicate a possible structural phase transition occurring for a value of temperature in the range [130 K, 180 K]. Differential Scanning Calorimetry (DSC) measurements were also performed for pilocarpine clorohydrate and the results point to a new, first order phase transition occurring at 463 K.